2023
DOI: 10.4300/jgme-d-22-00333.1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Household Income, and Mentorship Among Interns Who Are Underrepresented in Medicine

Abstract: Background Underrepresented in medicine (UIM) interns have unique lived experiences that affect their paths to medicine, and more information is needed for medical residency and fellowship programs to better support them. Objective We describe self-reported differences between UIM and White physician interns in key demographic areas, including household income growing up, physician mentorship, and adverse childhood experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…25 The intersection of race, ethnicity, and socioeconomic status in medical matriculation is well established, with URiM applicants and trainees more likely to have lower childhood household incomes and fewer options for financial support. 7 Specific to the financing of resident education, the application and interview process alone is expensive, 26 and 60% of residents are rent-burdened, as defined as 30% or more of first year gross monthly salary captured by the mean local monthly rent index. Rent-burdened institutions are also less likely to offer housing-related benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The intersection of race, ethnicity, and socioeconomic status in medical matriculation is well established, with URiM applicants and trainees more likely to have lower childhood household incomes and fewer options for financial support. 7 Specific to the financing of resident education, the application and interview process alone is expensive, 26 and 60% of residents are rent-burdened, as defined as 30% or more of first year gross monthly salary captured by the mean local monthly rent index. Rent-burdened institutions are also less likely to offer housing-related benefits.…”
Section: Discussionmentioning
confidence: 99%
“…One study of interns at a single academic center found all interns, whether white or Under-Represented in Medicine (URiM), grew up in households on average more affluent than the general population. 7 To better evaluate the Matthew effect, and by proxy the role of childhood household income, in the matriculation to residency, this study was designed to determine the proportion of applicants to a single ophthalmology residency program over a 5-year period that explicitly and voluntarily indicated they had a physician or doctor as a parent.…”
mentioning
confidence: 99%